2019
DOI: 10.12659/ajcr.914092
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Ductal Carcinoma Arising in Mucinous Cystic Neoplasm of Pancreas: A Case Report

Abstract: Patient: Female, 40 Final Diagnosis: Invasive ductal carcinoma arising in mucinous cystic neoplasm of pancreas Symptoms: None Medication: — Clinical Procedure: Surgical resection Specialty: Oncology Objective: Rare co-existance of disease or pathology Background: Mucinous cystic neoplasm (MCN) of the pancreas is a rare mucin-producing cystic neoplasm that has a characteristic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Thus, pattern of invasion is a strong prognostic histological parameter in MCN-AIC. This finding is supported by evidence from other studies: T1a and T1b invasive carcinomas arising from ovarian-type stroma, septa and cystic capsule have a long-term disease-free survival [9,31] . In our study the role of lymph node invasion could not be addressed due to the sample limitations.…”
Section: Prognosissupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, pattern of invasion is a strong prognostic histological parameter in MCN-AIC. This finding is supported by evidence from other studies: T1a and T1b invasive carcinomas arising from ovarian-type stroma, septa and cystic capsule have a long-term disease-free survival [9,31] . In our study the role of lymph node invasion could not be addressed due to the sample limitations.…”
Section: Prognosissupporting
confidence: 81%
“…This finding is supported by evidence from other studies: T1a and T1b invasive carcinomas arising from ovarian-type stroma, septa and cystic capsule have a long-term disease-free survival. [9,31] In our study the role of lymph node invasion could not be addressed due to the sample limitations. But another large retrospective study indicated that lymph node positivity is the most important factor for decreased survival of MCN-AIC, [32] a phenomenon also observed in a case report.…”
Section: Prognosismentioning
confidence: 97%
“…In the above‐mentioned studies, however, detailed information on the size of the invasive component or their pTNM classification was not given. More recently, two studies [ 4 , 20 ] provided evidence that T1a/T1b MCN‐AIC, which was limited to the ovarian‐type stroma, cystic septa, or hyalinized stroma in the superficial layer of the cyst wall, had excellent survival similar to noninvasive MCN. These four cases were all at relatively early stages of invasion with invasive foci measuring up to 0.7 cm…”
Section: Discussionmentioning
confidence: 99%
“…As for MCN‐AICs, Hui et al [ 4 ] presented three well‐documented T1a/T1b MCN‐AICs with favorable prognosis and advocated for regular follow‐up to reduce the use of systemic chemotherapy. A case report from Japan also showed a T1a MCN‐AIC patient who recovered without chemotherapy (the patient ceased chemotherapy after experiencing significant adverse reactions) [ 20 ]. All these four cases had invasion limited to ovarian‐type stroma, cyst septa, or the cyst capsule which might be identified as ‘encapsulated’ by our definition.…”
Section: Discussionmentioning
confidence: 99%
“…Ohtsuka et al reported on a long-term retrospective nationwide study of MCNs with OS and identified five factors predicting malignancy of MCNs: age 56 years or older, high serum CEA level, high CA19-9 level, tumor size ≥ 51 mm, and the presence of mural nodules [13]. However, Sawai et al reported a rare case of a moderately differentiated invasive ductal carcinoma measuring up to 0.5 cm in diameter in the superficial layer of the cyst wall in the OS [14]. Lewis et al found that invasive carcinoma confined to the OS of MCNs had an excellent prognosis [9].…”
Section: Discussionmentioning
confidence: 99%